1998
DOI: 10.1038/1765
|View full text |Cite
|
Sign up to set email alerts
|

A missense mutation in the αB-crystallin chaperone gene causes a desmin-related myopathy

Abstract: Desmin-related myopathies (DRM) are inherited neuromuscular disorders characterized by adult onset and delayed accumulation of aggregates of desmin, a protein belonging to the type III intermediate filament family, in the sarcoplasma of skeletal and cardiac muscles. In this paper, we have mapped the locus for DRM in a large French pedigree to a 26-cM interval in chromosome 11q21-23. This region contains the alphaB-crystallin gene (CRYAB), a candidate gene encoding a 20-kD protein that is abundant in lens and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
830
2
27

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,006 publications
(892 citation statements)
references
References 27 publications
22
830
2
27
Order By: Relevance
“…Our studies of cultured human muscle fibers bearing the transthyretin Val122Ile mutation and overexpressing AβPP indicated that increased muscle fiber degeneration is associated with increased Aβ oligomerization [11]. Of interest is a recent study related to cultured cardiomyocytes which experimentally expressed both αBC bearing the R120G mutation, causing desmin-related myopathy [30], and a toxic amyloidogenic peptide PQ81 [31]. Those cardiomyocytes had pronounced aggresome formation but, interestingly, inhibition of the aggresome formation through additional expression of the wild αBC led to increased accumulation of PQ81 amyloidoligomers and increased cellular toxicity [31].…”
Section: Discussionmentioning
confidence: 97%
“…Our studies of cultured human muscle fibers bearing the transthyretin Val122Ile mutation and overexpressing AβPP indicated that increased muscle fiber degeneration is associated with increased Aβ oligomerization [11]. Of interest is a recent study related to cultured cardiomyocytes which experimentally expressed both αBC bearing the R120G mutation, causing desmin-related myopathy [30], and a toxic amyloidogenic peptide PQ81 [31]. Those cardiomyocytes had pronounced aggresome formation but, interestingly, inhibition of the aggresome formation through additional expression of the wild αBC led to increased accumulation of PQ81 amyloidoligomers and increased cellular toxicity [31].…”
Section: Discussionmentioning
confidence: 97%
“…HSPB5 and HSPB7 are normally enriched at sarcomeres at the Z disk and are essential for actin anchoring, indicating a primary role in con trolling sarcomere homeostasis. Cardiomyocytes with a CRYAB R120G mutation have an irregular sarcomeric struc ture and defective chaperone like function, which can trigger desmin related myopathy and early onset cardio myopathy 90,91 . Whether the effect of the mutation results from gain of toxic function or loss of function of the wild type protein or protein complex remains unknown.…”
Section: Derailment Owing To Genetic Mutationsmentioning
confidence: 99%
“…These three proteins are present in great abundance in muscle tissue. According to Vicart et al (1998), their high expression level would allow them to exert an intermediate protective effect in response to stress conditions with no lag time necessary for protein synthesis. They constitute a dynamic complex (Sun and MacRae, 2005).…”
Section: Hspsmentioning
confidence: 99%